DIKSI, CITRAAN, DAN MAJAS PADA PUISI ’’AKU MENUNGGU BUNGA’’ KARYA HERI ISNAINI’’ - Najwa Fadilanitaa; Khofifah Indar F; Arneta Destria (Pusat Riset dan Inovasi Nasional, 2022)
This study discusses the use of diction, imagery, and figure of speech in the poem Aku Waiting for the Flower. The poem I Wait for Flowers is a poem that talks about someone who is waiting for someone they love very much. With beautiful poetry lines and contains very strong meanings and meanings. This study aims to: 1) Describe Diction 2) Explain imagery 3) Describe the figure of speech in the poem Aku Waiting Bunga. This research uses qualitative descriptive research. The data collection technique used is reading and note-taking technique and data analysis technique using descriptive analysis technique which includes description, classification, and analysis. The results of the research on the poem ''I am waiting for the flower'' have denotative and connotative diction, visual imagery, feeling imagery, and imagery. intellectual, as well as figure of speech personification and hyperbole